Synthesis of Benzofuran Derivatives and their Evaluation of Antimicrobial Activity - D. R. Harish Kumar; M. D. Karvekar (E-Journal of Chemistry)
2-Acetyl benzofuran (1) was synthesized by refluxing salicylaldehyde and dry chloroacetone in presence of potassium carbonate. The product formed was reacted with 2-aminobenzothiazole with catalyst p-toluene sulphonic acid to form N-[(1Z)-1-(benzofuran-2-yl)ethylidene]1,3-benzothiazol-2-amine (2). In cold condition, Staudinger reaction was carried out for compound (2) with various acid chlorides in presence of triethylamine to synthesize 4-[1-benzofuran-2-yl]-1-[1, 3-benzothiazol-2-yl]-4-methylazetidin-2-one (3a-3j). All the synthesized compounds were characterized on the basis of analytical data. The compounds were screened for their antimicrobial activities. Compound 3b,3cand 3d exhibited moderate activity.